BoLA‐1 antibodies and the induction of bovine neonatal pancytopenia: a twin calves study. Issue 1 (29th July 2014) - Kasonta, Rahel; Sauter‐Louis, Carola; Holsteg, Mark; Cussler, Klaus; Bastian, Max
Abstract : Bovine neonatal pancytopenia (BNP) is a vaccine‐induced alloimmune disease. The syndrome affects young calves and is characterised by haemorrhages, pancytopenia and severe destruction of the haematopoietic tissue. Recent evidence indicates that vaccine‐induced alloantibodies target bovine major histocompatibility complex class I (MHC‐I) antigens (bovine leucocyte antigen 1 (BoLA‐1)). However, whether BoLA‐1‐specific antibodies suffice to induce BNP is still a matter of debate. In the current case study, we investigate samples from twin calves where only one calf succumbed to BNP. The fraternal twin also ingested high amounts of BoLA‐1‐specific alloantibodies but it did not develop BNP because the maternal antibodies did not recognise its BoLA‐1 alleles. This association between lack of BoLA‐1 binding and the absence of disease provides another important piece of evidence that BoLA‐1‐specific alloantibodies play a role in the induction of BNP.